Alleviating Parenting Stress in Parents with Intellectual Disabilities: A Randomized Controlled Trial of a Video‐feedback Intervention to Promote Positive Parenting. Issue 3 (23rd November 2016) - Hodes, Marja W.; Meppelder, Marieke; de Moor, Marleen; Kef, Sabina; Schuengel, Carlo
Abstract : Background: Adapted parenting support may alleviate the high levels of parenting stress experienced by many parents with intellectual disabilities. Methods: Parents with mild intellectual disabilities or borderline intellectual functioning were randomized to experimental ( n = 43) and control ( n = 42) conditions. Parents in both groups received care‐as‐usual. The experimental group also received an adapted version of video‐feedback intervention for positive parenting and learning difficulties (VIPP‐LD). Measures of parenting stress were obtained pre‐test, post‐test and 3‐month follow‐up. Results: Randomization to the experimental group led to a steeper decline in parenting stress related to the child compared to the control group ( d = 0.46). No statistically significant effect on stress related to the parent's own functioning or situation was found. Conclusions: The results of the study suggest the feasibility of reducing parenting stress in parents with mild intellectual disability (MID) through parenting support, to the possible benefit of their children.